Mengungkap Penggunaan, Pelaporan, dan Akuntabilitas Alokasi Dana Desa - Nurul Fuada; Haliah; Nirwana; Syamsuddin; Andi Kusumawati (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2024)
This study delves into the utilization, reporting, and accountability of Village Fund Allocation in Panciro Village. Adopting a phenomenological approach, data were collected through budget realization reports and interviews with village officials. The results reveal that Panciro Village adheres sufficiently to financial management protocols, as evidenced by proper documentation in the cash book and timely submission of reports to higher authorities. However, while current accountability mechanisms are functional, the abstract lacks an in-depth exploration of the specific strategies employed and the challenges faced in ensuring transparency and preventing fund misappropriation. Moreover, the abstract would benefit from contextualizing the findings through comparative analysis with neighboring villages or national standards. Additionally, future research could involve longitudinal studies to evaluate the sustainability of the implemented accountability measures and their long-term impact on village development.